Professionalism of Fiqh Teachers in Improving Student Learning Outcomes at MTs Negeri 12 Indramayu - Alya Nur Rahma (Manajia: Journal of Education and Management, 2025)
This study aims to discuss the professionalism of fiqh teachers in improving student learning outcomes at MTs Negeri 12 Indramayu. Because the role of teacher professionalism is something that must be possessed by a teacher, including a fiqh teacher. Because the professionalism of a teacher has a very dominant role in teacher competence, even though the sophistication of technology is already very impressive. With a qualitative approach research and field study type. The results of this study show how big the teacher factor is in helping students learn, so teachers must have a professional attitude. So that it can be that a good relationship between a teacher and students will make students love their teachers and students will like fiqh subjects, and allow students to learn as well as possible. An educator revealed that school factors influence learning including teaching methods, teacher-student relationships, curriculum, learning methods, and homework.